Auswertung fünfjähriger Lichtfallenfänge (1984-1988) auf der Phänobasis Hohenfinow (Kreis Eberswalde-Finow) für die Lepidopteren-Faunistik. - Richert, Arnold; Hülbert, Dieter (Contributions to Entomology = Beiträge zur Entomologie, 1991)
This paper informs about extended evaluations of the catches by light traps made daily over five years (1984 to 1988) for the faunistics of Lepidoptera on the phenological basis of Hohenfinow. Apart from the 13 nocturnal species of butterflies whose control was obligatory as part of the pest control in the plant protection service of the GDR, the determination of all the species of Lepidoptera caught established for Hohenfinow 51 species of tiger moths, silkworm moths, hawk-moths and carpenter moths, 152 species of owlet moths, and 33 species of geometrid moths, among them all 19 rare species or such that were newly established in this area after a ling time. 29 species were established for the first time in the habitat of the locations of the light traps. One of thes species has the northern border of its distribution in this area. A cooperation with faunists interested in Lepidoptera could in the same way combine in many locations of light traps the practical pest control with a further contributions to the survey of Lepidoptera of the GDR.